Back Cover Image, Volume 92, Number 11, November 2020. Issue 1 (29th December 2020) - Ruan, Zijing; Liu, Chao; Guo, Yuting; He, Zhenqing; Huang, Xinhe; Jia, Xu; Yang, Tai
Abstract : Back Cover Caption : The cover image is based on the Research Article SARS‐CoV‐2 and SARS‐CoV: Virtual Screening of Potential inhibitors targeting RNA‐dependent RNA polymerase activity (NSP12) by Zijing Ruan et al., https://doi.org/10.1002/jmv.26222 .